Synthesis Of Large Area Graphene And Graphene Flake Via Chemical Vapor Deposition Using Copper Catalyst And Methane - Mohd Zuhan, Mohd Khairul Nizam (2018)
Graphene is a two-dimensional material arranged in hexagonal honeycomb structures and is a single layer of graphite. Several fascinating properties of graphene such as a very conductive and highly transparent material is expected to contribute significantly towards the advancement of electronics, solar cell, composites, and medical sector. In this study, atmospheric chemical vapour deposition (APCVD) was used as synthesis method. Methane was used as carbon feedstock, nitrogen as a carrier gas and hydrogen as reducing agent for two types of graphene synthesis which is large area graphene (lateral size >1 cm2) and graphene flakes (lateral size <1 µm2) with Cu was used as a catalyst. The study is also focusing on solving the tendency of polycrystalline large area graphene from breaking into small fragments during the transfer process via wet etching by reducing the surface tension of graphene/water interface using n-heptane as support and avoiding polymer contamination on the graphene. The proposed method is easier and more environmentally friendly as the practice reduce the use copious amount of organic solvent to remove the polymer layer as the process often creates plentiful of chemical waste. N-heptane as support material for wet etching process is easier to conduct, generated less waste and does not cause significant contamination on the graphene and can be reused for another graphene transfer and create less toxic waste as compared by using polymer support. In addition, a wet etching method requires the use of an etchant and the process produce wastes contain metal that generally disposed of in single-use. The practice limits the use of the metal substrate and harmful to the environmentally. Hence, recovery of the metal from the waste as a precursor to a new form of catalyst for graphene flake synthesis is suggested. The study utilised 30 sccm and 50 sccm of CH4 gases flow-rate with reaction time were set for 30 min and 60 min with growth temperature was set at 950 °C for large area graphene synthesis. Nine metal foils were used in three zones locations inside the horizontal tubular furnace. Furthermore, the effect of H2 flow rate on graphene crystallinity which was set at 0, 25, 50, 75, 100, 125 and 150 sccm was also studied. Subsequently, graphene transfer from Cu foil onto Si/SiO2 was performed using 0.1 mol ammonium persulfate solution as an etching solution and n-heptane as supporting layer. Next, the etched Cu foil was recovered and reused by heat treatment temperature of 800 °C for 3 hours to obtain CuO for graphene flakes synthesis. Two formulations of 10% MgO with 90% CuO and 1% MgO with 99% CuO were dispersed in ethanol and was kept overnight in an oven at 60 °C before undergoing calcination process at 950 °C to produce CuO/MgO that was used for graphene flake synthesis. The graphene flakes synthesis was conducted at 950 °C for 60 min with 10 sccm of CH4. Thermogravimetric analysis (TGA), X-Ray Diffraction (XRD), X-ray Fluorescence (XRF), optical imaging, Raman spectroscopy (single point and mapping), high-resolution transmission electron microscopy (HRTEM), Field emission scanning electron microscopy (FESEM), and X-Ray Photoelectron Spectroscopy (XPS) were used to evaluate the properties of the synthesized graphene and CuO/MgO. The result shows large area graphene and graphene flakes were successfully synthesized using Cu foil and recovered Cu, the positions of the Cu shows the different quality of graphene and the hydrogen flow rates shows the quality of the graphene is affected by the hydrogen flow rates with positive effect on graphene formation at 50 to 100 sccm and negative effect when no (0 sccm), inadequate (25 sccm) or excessive (>125 sccm) hydrogen flow rates were supplied. The locations of the catalyst at zone 1 and zone 2 of the horizontal furnace show good graphitic structure formation while at zone 3 amorphous carbon formation is more dominant. N-heptane is found as a useful material for large area graphene transfer that reduces contamination on graphene surface. Cu from etching solution waste can be reused for CuO formation and graphene flakes synthesis using a similar method for synthesis of large area graphene. In conclusion, the catalyst locations in the horizontal CVD and hydrogen flow rates play an important factor in graphene formation. The transfer method using the n-heptane as support layer assisting in graphene transfer process that reduces contamination and damage to graphene structure. Also, the graphene flakes have been successfully synthesized using the CuO / MgO catalyst obtained from recovered Cu.